2023
DOI: 10.1021/acsnano.2c11278
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Magneto-Softening of 3D Hydrogel Reverses Malignant Transformation of Cancer Cells and Enhances Drug Efficacy

Abstract: High extracellular matrix stiffness is a prominent feature of malignant tumors associated with poor clinical prognosis. To elucidate mechanistic connections between increased matrix stiffness and tumor progression, a variety of hydrogel scaffolds with dynamic changes in stiffness have been developed. These approaches, however, are not biocompatible at high temperature, strong irradiation, and acidic/basic pH, often lack reversibility (can only stiffen and not soften), and do not allow study on the same cell po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 103 publications
(177 reference statements)
2
13
0
Order By: Relevance
“…[118] Readers are encouraged to refer to published papers for the advantages and limitations of these approaches. [25,26]…”
Section: Stiffnessmentioning
confidence: 99%
See 2 more Smart Citations
“…[118] Readers are encouraged to refer to published papers for the advantages and limitations of these approaches. [25,26]…”
Section: Stiffnessmentioning
confidence: 99%
“…[23,24] These stimuli-responsive hydrogels have been shown in proofof-concept studies to direct targeted cellular responses, and some have even led to appreciable outcomes for disease treatment. [25] There are significant technical obstacles to replicate the native ECM in vitro. One of the major difficulties is simulating the native dynamic structural remodeling of ECM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings revealed that matrix stiffening promoted malignancies, while matrix softening downregulated the expression of mechano-transductors. 24 While, in that study, the whole matrix stiffness could be rapidly altered to measure downstream effects, the influence of dynamic mechanical compression and strain of the network generated from individual point sources, like individual cells, remains to be studied. This work applies magnetically controlled microscale actuation of 3D tumor invasion assays over several days of culture.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that matrix stiffening promoted malignancies, while matrix softening downregulated the expression of mechano-transductors. 26 While, in that study, the whole matrix stiffness could be rapidly altered to measure downstream effects, the influence of dynamic mechanical compression and strain of the network generated from individual point sources, like individual cells, remains to be studied.…”
Section: Introductionmentioning
confidence: 99%